Implementasi Sustainability Reporting Pada Perusahaan Yang Termasuk Ke Dalam Indeks LQ45 - Annisa Nurfitriana (Journal of Economics Development Issues, 2020)
Sustainability reporting is one of report includes economics, environment, and social dimensions. Because of stakeholders need financial and non financial informatio. So, this research purpose to determine implementation of sustainability reporting in companies includes LQ45 index. This research uses desriptive method and data analysis used content analysis approach. The population are 45 companies and sampling technique using purposive sampling. So the sample are 28 companies. The results of this research are the implementation of sustainability reporting still average category. However, there are several sector as low category namely various industrial sectors, the consumer goods industry, the basic chemical industry, finance, investment trading services, as well as residential and construction properties.